Numerical Capacity Profile of Eleventh-Grade High School Students in Stoichiometry - Fauziah, Ita Septiana; Ardhana, Ivan Ashif (Universitas Negeri Malang, 2024)
PISA results for 2022 report that Indonesian student's numeracy skills have improved. However, the results are still below the global average and require continuous improvement. One attempt to enhance student's numeracy skills is by providing numeracy-based assessments that can be applied to chemistry subjects, one of which is stoichiometry. The study aims to identify and describe the numeracy profile of eleventh-grade high school students on stoichiometry. The method used is quantitative descriptive. The study subjects were eleventh-grade high school students who had received stoichiometry instruction. The instruments used consisted of nine questions that were validated and empirically tested (reliability score of 0.528, indicating a fairly reliable category). The study results showed that the students' numerical abilities obtained an average score of 67%, which was categorized as good. The percentage of students in the excellent category was 26%, in the good category was 47%, in the sufficient category was 24%, and in the less-than-sufficient category was 3%. The indicator accuracy rate was 61% for analyzing information such as tables, charts, and diagrams, 80% for using numbers and symbols, and 56% for interpreting analysis results. Numeracy skills in chemistry, particularly in stoichiometry, are crucial for achieving learning objectives and supporting global efforts toward quality education, as aligned with the SDGs. Enhancing these skills equips students with better problem-solving abilities in academics and real-life situations.